Fiscalía 36, Infancia y adolescencia SRPA (2020)
The purpose of this degree work is to present the professional experience that was carried out in the 36th sectional Prosecutor's Office of the childhood and adolescence unit of Duitama-Boyacá, under the modality of internship, this experience had a duration of 240 hours, and it was carried out remotely by the COVID-19 pandemic that is present in the world. In this practice, all the knowledge and skills learned at the Antonio Nariño University, Duitama headquarters, within the law school, were handled. The professional practice carried out in the 36th section of the Childhood and Adolescence Prosecutor's Office was carried out as a requirement to achieve the professional title, its objective was to achieve new skills and thus apply them in professional life; In the same way, new knowledge was obtained, with the work of the sectional Prosecutor's Office 36, such as studying files, projecting orders from the Prosecutor, and suggesting decisions to be taken, that is, formulation of imputation, indictment documents, legalization orders capture, investigation file, among others. This practical report will emphasize the activities developed, and the relevant information regarding the work carried out in the sectional Prosecutor's Office 36. In this way, data will be reflected on the agency where the practice was carried out, such as the mission, vision, organizational structure and in the final part are the annexes that demonstrate the legitimacy of the practice.